PERAN LAKI-LAKI DAN PEREMPUAN DALAM KEJADIAN 1-3 DAN IMPLIKASI TERHADAP PASTORAL DI GEREJA MASEHI INJILI DI MINAHASA JEMAAT YERUSALEM PAAL DUA MANADO - Melissa M.F. Waturandang; Leonardo Caesar Dendeng (Institut Agama Kristen Negeri Manado, 2020)
ABSTRACT The purpose of this study is (1) analyzing the roles of men and women in Genesis 1-3, (2) identifying and analyzing the roles of men and women in the family in the Church (3) analyzing and describing the pastoral church about the role of men and women in the family of the Church. This research is a qualitative study, with a socio-historical analysis to analyze the text of Genesis 1-3, at the Evangelical Christian Church in Minahasa (GMIM) of the Jerusalem Paal Dua Church in Manado in 2018. Data is collected through interpretation, observation, interview and documentation study. From the results of the analysis and interpretation of the data obtained an indication that: (1) the roles of men and women in Genesis 1-3 are not equal, where men are still higher, according to the context in the agrarian society at that time (2) the role of men men and women in the family even though it is in the context of a networked society but still unequal, where men are still higher as in an agrarian society because the congregation still reads the Bible without knowing the context of writing (3) the Church still has not seen the role of men and women who equivalent as something important in pastoral care because it indirectly still preserves patriarchal views as in agrarian societies. From these findings it is recommended that (1) the congregation read the Bible according to the context because even though the message of the Word of God remains the same but the context and readers change (2) the church in pastoral ministry is advised to teach the congregation to read the Bible according to context, not to be constrained by the context at the time of writing The Bible but teaches the liberating Word of God and dynamic faith.